Opisthorchis felineus in Ryazan region - O. N. Andrejanov; V. V. Gorohov; R. T. Safiullin; A. V. Hrustalev; A. S. Moskvin (Российский паразитологический журнал)
At carnivores in Ryazan region Opisthorchis felineus has been revealed. Trematodes are diagnosed in a liver of an ordinary fox (Vulpеs vulpеs) at mixed infection. Carnivorous are infected at 6,25 %. It is the first case of opisthorchosis in the region.